PEMAHAMAN KONSEP, PRINSIP, DAN DASAR JIHAD DALAM PERSPEKTIF AL-QUR’AN - Muhammad Shohib (Universitas Kiai Abdullah Faqih (UNKAFA) Gresik, 2022)
This paper seeks to express the Understanding of the Concepts, Principles, and Basics of Jihad according to the Qur'an with a thematic interpretation approach. It is expected to be a lamp that illuminates the people, that the Qur'an never justifies terrorism that justifies all means in fighting for the establishment of islamic teachings. The problem of terrorism in the name of jihad is indeed a difficult problem for all elements of the Muslim community. Muslims in Indonesia are no exception. Where this nation continues to face the problem of violence and terrorism that has been going on after independence and still continues today.Kata kunci : Jihad, perspektif, pemahaman